Obsessive-compulsive disorder and temporal lobe porencephaly: a case report - Gaoju Deng; Yuan Cao; Changjian Qiu (BMC Psychiatry)
Abstract Background The functional and structural abnormalities of cortico-striato-thalamo-cortex have been reported to be associated with the neurobiological basis of obsessive–compulsive disorder (OCD). OCD can also occur in the striatum damaging after brain infarction, which is called OCD caused by physical diseases. The relationship and mechanism between temporal lobe abnormalities and OCD are still unclear. Case presentation A young male with temporal lobe porencephaly presented with obsessive–compulsive symptoms. The cognition of this OCD participant was not significantly impaired, and his social function was well maintained. After treatment with sertraline, aripiprazole, and fluvoxamine, he was improved but relapsed several times after drug withdrawal. However, the therapeutic effect was sustained upon reinitiation of the medication. Conclusion This is the first reported case of OCD in an individual with left temporal lobe porencephaly. The possible relationship between obsessive–compulsive symptoms and temporal lobe structural abnormalities needs to be further studied. The maintenance treatment and prognosis of organic obsessive–compulsive disorder also deserve further study.